A néptanítói szakismeretek konstrukciós folyamatai a 20. század elején: A Néptanítók Enciklopédiája alapján (1911-1915) - Németh, András (Magyar Pedagógia, 2013)
In the formation process experienced by two clearly defined groups of teachers (elementary school teachers and teachers at higher levels) in the second half of the 19th century, we can see the evolution of two different cultures and teaching competencies. This paper examines the historical aspects of the construction of these two competencies, in which the different professions create the symbolic and material worlds and knowledge content of their identity. The study concentrates on the characteristics of the Central European region, specifically on those of Hungary. I used the Encyclopaedia of Elementary School Teaching, a professional periodical for Hungarian teachers, as a source. In its conceptual system and research methodology, the approach transcends the perspective of historical sociology, which concentrates on macro-processes. This descriptive, expository analysis is based on qualitative research methodology tools.